PENYULUHAN TENTANG MENUMBUHKAN MINAT BERWIRAUSAHA DI KALANGAN REMAJA UNTUK MEMBENTUK KARAKTER WIRAUSAHA YANG KREATIF DAN INOVATIF - Rossa Ayuni; Meirani Meirani; Helmarini Helmarini; Anisa Martiah; Duharman Duharman (Batara Wisnu : Indonesian Journal of Community Services, 2022)
The goal to be achieved in this activity is to provide knowledge about the importance of growing interest in entrepreneurship among teenagers to prepare a competitive young generation because competition is not enough just with education but requires skills such as entrepreneurship in order to open a new business world and shape character. Creative and innovative entrepreneur. The method used in delivering the material is a lecture using a laptop, LCD and powerpoint slides as well as question and answer or discussio